A review of ice and tide observations in the Bay of Fundy - Desplanque, Con; Mossman, David (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1998)
Vigorous quasi-equilibrium conditions characterize interactions between land and sea in macrotidal regions. Ephemeral on the scale of geologic time, estuaries around the Bay of Fundy progressively infill with sediments as eustatic sea level rises, forcing fringing salt marshes to form and reform at successively higher levels. Although closely linked to a regime of tides with large amplitude and strong tidal currents, salt marshes near the Bay of Fundy rarely experience overflow. Built up to a level about 1.2 m lower than the highest astronomical tide, only very large tides are able to cover the marshes with a significant depth of water. Peak tides arrive in sets at periods of 7 months, 4. S3 years and 18.03 years. Consequently, for months on end, no tidal flooding of the marshes occurs. Most salt marshes are raised to the level of the average tide of the 18-year cycle. The number of tides that can exceed a certain elevation in any given year depends on whether the three main tide-generating factors peak at the same time. Marigrams constructed for the Shubenacadie and Cornwallis river estuaries, Nova Scotia, illustrate how the estuarine tidal wave is reshaped over its course, to form bores, and varies in its sediment-carrying and erosional capacity as a result of changing water-surface gradients. Changing seasons bring about dramatic changes in the character of the estuaries, especially so as ice conditions develop during the second half of the 206-day (7-month) cycle when the difference in height between neap tide and spring tide is increasing, the optimal time for overflow in any season. Maximum ice hazard, including build-up of "ice walls" in Fundy estuaries, occurs one or two months before perigean and spring tides combine to form the largest tide of the cycle. Although "ice walls" and associated phenomena pose hazards for man-made constructions, important natural purposes are served which need to be considered in coastal development and management schemes.